2010
DOI: 10.1029/2009gl041572
|View full text |Cite
|
Sign up to set email alerts
|

Surface water–groundwater exchange in transitional coastal environments by airborne electromagnetics: The Venice Lagoon example

Abstract: [1] A comprehensive investigation of the mixing between salt/fresh surficial water and groundwater in transitional environments is an issue of paramount importance considering the ecological, cultural, and socio-economic relevance of coastal zones. Acquiring information, which can improve the process understanding, is often logistically challenging, and generally expensive and slow in these areas. Here we investigate the capability of airborne electromagnetics (AEM) at the margin of the Venice Lagoon, Italy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 25 publications
0
48
0
1
Order By: Relevance
“…This holds for both the surface and subsurface environments. Investigations carried out over recent years Viezzoli et al, 2010) revealed that fresh groundwater resources are found at quite low depths, i.e., 30-40 m and even less than 10 m beneath the lagoon bottom. Like the hydrogeological settings of other lagoons (e.g., Santos et al, 2008), the silty-clayey layer marking the boundary between the marine Holocene and continental Pleistocene deposits precludes or at least reduces the vertical leakage of the salt waters downward into the un- derlying freshwater aquifers.…”
Section: Main Insightsmentioning
confidence: 99%
“…This holds for both the surface and subsurface environments. Investigations carried out over recent years Viezzoli et al, 2010) revealed that fresh groundwater resources are found at quite low depths, i.e., 30-40 m and even less than 10 m beneath the lagoon bottom. Like the hydrogeological settings of other lagoons (e.g., Santos et al, 2008), the silty-clayey layer marking the boundary between the marine Holocene and continental Pleistocene deposits precludes or at least reduces the vertical leakage of the salt waters downward into the un- derlying freshwater aquifers.…”
Section: Main Insightsmentioning
confidence: 99%
“…This is particularly true for data collected by airborne electromagnetic methods (AEM) because they can be collected quickly, densely, and at a relatively low cost for the very large spatial coverage (Steuer et al, 2008;Viezzoli et al, 2010b;Abraham et al, 2012;Faneca Sànchez et al, 2012;Refsgaard et al, 2014;Munday et al, 2015). Large-scale AEM (or ground-based EM) investigations have been used to delineate aquifers, aquitards, and buried valleys or other structures containing aquifers Jørgensen et al, 2003;Abraham et al, 2012;Oldenborger et al, 2013), to assess aquifer vulnerability Foged et al, 2014), to map saltwater intrusion (Fitterman and Deszcz-Pan, 1998;Viezzoli et al, 2010b;Lawrie et al, 2012;Herckenrath et al, 2013b), and to map freshwater resources (Steuer et al, 2008;Faneca Sànchez et al, 2012;Munday et al, 2015).…”
Section: Informing Hydrologic Models With Geophysicsmentioning
confidence: 99%
“…For example, this is fairly common at landfills and waste dump sites [1][2][3], saline disposal basins [4], seawater inundation along coastal aquifers [5], and in estuaries [6][7][8][9][10][11]. Typically, when saltwater and freshwater are in contact with each other, the groundwater flow is due to natural hydraulic gradients, and the movement of the fluid is termed "forced" convection.…”
Section: Forced Free and Mixed Convective Flowmentioning
confidence: 99%